Re-used or New Bedding Are Not Drivers of Salmonella Levels and Serovar Emergence in Commercially Farmed Broilers in Australia - Chinivasagam, Helene Nalini; Estella, Wiyada; Rodrigues, Hugh; Mayer, David G.; Tran, Thuy; Onysk, Agnieszka; Weyand, Caitlin; Diallo, Ibrahim; Billington, Craig (Frontiers in Sustainable Food Systems, 2022)
To inform Salmonella on-farm management during broiler rearing, a two-year study on two farms compared the Australian practices of new bedding use, partial litter re-use and an alternative, full litter re-use. Six sequential commercial cycles of 50 days each were tested on each farm, on day 7 from placement (litter only), prior to first thin-out and prior to final removal (litter and caeca). A random number sample collection occurred, defined by shed supports (33, 39), different drinkers, feeders and shed center. Across the six cycles on both farms, Salmonella levels in ceca just prior to thin-out on full re-use litter were higher (log 3.11 MPN/g, P=0.008) than for new bedding (log 2.04 MPN/g) and partial re-use (log 2.43 MPN/g) litter (the latter two were not significantly different). Prior to final removal across all practices the Salmonella levels in caeca from new bedding (log 1.72 MPN/g), partial re-use litter (log 1.77 MPN/g) and full re-use litter (log 2.33 MPN/g) were not statistically different, suggesting no effect of litter practice. The Salmonella levels in litter prior to the first (log 1.96 – 2.31 MPN/g) and second (log 2.24 – 2.48 MPN/g) removals were also not statistically different. The emergence of Salmonella serovars in the partitioned chicken-free grow-out end (back) of all sheds at day 7 did not suggest carry-over. Both the pattern of emergence of Salmonella serovars and Salmonella levels in litter day 7 in the brooder-end with chickens (front), suggested the Salmonella present were due to flock contribution and not practice driven. The dominant Salmonella serovar across cycles on both farms was S. Sofia (75%, and 77% isolates) followed by S. Typhimurium (8% and 17%). Irrespective of initial serovars, Salmonella Sofia rapidly gained dominance and displaced thirteen other serovars including S. Typhimurium on both farms. This study demonstrates that the litter practices are not the major driver of Salmonella prevalence in broiler farming, supporting the commercial re-use of bedding as a sustainable farming practice in Australia. The major contributor of Salmonella load in production is the Salmonella status of incoming flock, indicating this is the key for focus future control measures.